Pengaruh Pelatihan dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Dinas Tenaga Kerja dan Transmigrasi Provinsi Sulawesi Selatan - Andi Saharuddin; Kamaruddin Kamaruddin (Jurnal Online Manajemen ELPEI, 2022)
This study aims to test and find out how training and work discipline influence employee performance at the South Sulawesi Prov. South Sulawesi Manpower and Transmigration Office. Data collection uses primary data obtained from questionnaires using random sampling technique. The population is all employees of the South Sulawesi Province Manpower and Transmigration Office, the sample taken is 97 people. Methods of data analysis using simple linear regression techniques and multiple linear regression. The results showed that training and work discipline had a positive and significant effect on employee performance at the South Sulawesi Province Manpower and Transmigration Office.